'Climategate': Paradoxical Metaphors and Political Paralysis. (1st November 2010) - Nerlich, Brigitte
Abstract : Climate scepticism in the sense of climate denialism or contrarianism is not a new phenomenon, but it has recently been very much in the media spotlight. When, in November 2009, emails by climate scientists were published on the internet without their authors' consent, a debate began in which climate sceptic bloggers used an extended network of metaphors to contest (climate) science. This article follows the so-called 'climategate' debate on the web and shows how a paradoxical mixture of religious metaphors and demands for 'better science' allowed those disagreeing with the theory of anthropogenic climate change to undermine the authority of science and call for political inaction with regard to climate change.